Remote control : television, audiences, and cultural power - Seiter, Ellen, 1957-; Borchers, Hans; Kreutzner, Gabriele; Warth, Eva-Maria (Routledge library editions. Television, 2013)
The ways in which we watch television tell us much about our views of gender, the family and society. Bringing together the leading experts in the field of audience studies, this book investigates how viewers watch television, and what they think about the programmes they see. Originally published in 1989, the book is divided into two sections which discuss some of the theoretical issues at stake and then present case studies of a wide range of viewers: women office workers, Israeli watchers of Dallas, German families, the elderly, and American daytime soap fans. Contributors from Britain, the United States, Western Europe, Australia and Israel offer a wide range of perspectives, from feminism to post-modernism, and from semiotics to Marxism.